The effect of final annealing heating rate on abnormal grain growth in a Fe-3.5%Si steel - Citrawati, F.; Quadir, Md Zakaria; Munroe, P. (2017)
© 2017 Trans Tech Publications, Switzerland. In this study the effects of heating rate on the sharpness and size of Goss oriented ({110} < 001 > ) grains during secondary recrystallization annealing at 900 °C was observed. The results show that, at the same annealing temperature, rapid heating of the samples to this temperature generates a higher drag force compared to a slower heating rate (5°C/min). The two groups of samples show different growth kinetics for Goss grains, in which at the longest annealing time, the rapid heating sample exhibits larger maximum Goss grain size compared to the slower heated samples.